Deletion of α-neurexin II results in autism-related behaviors in mice - Dachtler, J (Transl Psychiatry, 2014)
Autism is a common and frequently disabling neurodevelopmental disorder with a strong genetic basis. Human genetic studies have discovered mutations disrupting exons of the NRXN2 gene, which encodes the synaptic adhesion protein α-neurexin II (Nrxn2α), in two unrelated individuals with autism, but a causal link between NRXN2 and the disorder remains unclear. To begin to test the hypothesis that Nrxn2α deficiency contributes to the symptoms of autism, we employed Nrxn2α knockout (KO) mice that genetically model Nrxn2α deficiency in vivo. We report that Nrxn2α KO mice displayed deficits in sociability and social memory when exposed to novel conspecifics. In tests of exploratory activity, Nrxn2α KO mice displayed an anxiety-like phenotype in comparison with wild-type littermates, with thigmotaxis in an open field, less time spent in the open arms of an elevated plus maze, more time spent in the enclosure of an emergence test and less time spent exploring novel objects. However, Nrxn2α KO mice did not exhibit any obvious changes in prepulse inhibition or in passive avoidance learning. Real-time PCR analysis of the frontal cortex and hippocampus revealed significant decreases in the mRNA levels of genes encoding proteins involved in both excitatory and inhibitory transmission. Quantification of protein expression revealed that Munc18-1, encoded by Stxbp1, was significantly decreased in the hippocampus of Nrxn2α KO mice, which is suggestive of deficiencies in presynaptic vesicular release. Our findings demonstrate a causal role for the loss of Nrxn2α in the genesis of autism-related behaviors in mice.